2013
DOI: 10.1002/smll.201202120
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Silver Nanoparticles in Macrophages

Abstract: Silver nanoparticles (nanosilver) are broadly used today in textiles, food packaging, household devices and bioapplications, prompting a better understanding of their toxicity and biological interactions. In particular, the cytotoxicity of nanosilver with respect to mammalian cells remains unclear, because such investigations can be biased by the nanosilver coatings and the lack of particle size control. Here, nanosilver of well-defined size (5.7 to 20.4 nm) supported on inert nanostructured silica is produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
160
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(169 citation statements)
references
References 43 publications
4
160
1
4
Order By: Relevance
“…It is still uncertain and currently under debate whether the toxicity of AgNPs is a particlespecific effect [42] or whether it is caused by the dissolution of Ag + ions [43,44]. In our system, the synergistic effect may be based on the coexistence of the drug with Ag + ions formed from slow AgNPs dissolution, once they are released from the protective polymeric shell.…”
Section: Discussionmentioning
confidence: 99%
“…It is still uncertain and currently under debate whether the toxicity of AgNPs is a particlespecific effect [42] or whether it is caused by the dissolution of Ag + ions [43,44]. In our system, the synergistic effect may be based on the coexistence of the drug with Ag + ions formed from slow AgNPs dissolution, once they are released from the protective polymeric shell.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several reports have found that the potential toxic effect caused by NS occurred only at high concentrations, and incorporated NS into biomaterials probably reduce the toxicity of NS. [11][12][13] Consequently, it is available to incorporate an optimized concentration of NS into a material to prepare an antibacterial wound dressing without cytotoxicity.…”
mentioning
confidence: 99%
“…Previous study indicates AgNPs may induce size dependent toxicity (Pratsinis et al, 2013). When the particle size is larger than 10 nm, the toxicity of AgNPs is primarily attributed to the dispersed particles rather than the released species due to its limited Ag + release (Pratsinis et al, 2013). It is further confirmed by Cronholm et al (2013), who showed that AgNPs entered into the cells in the form of particles, through intracellular uptake, with low amount of silver ion release.…”
Section: Discussionmentioning
confidence: 85%
“…As for metal nanoparticles that can release metal ions, one important question is whether the toxicity is mediated by the particles or the released ions. Previous study indicates AgNPs may induce size dependent toxicity (Pratsinis et al, 2013). When the particle size is larger than 10 nm, the toxicity of AgNPs is primarily attributed to the dispersed particles rather than the released species due to its limited Ag + release (Pratsinis et al, 2013).…”
Section: Discussionmentioning
confidence: 97%